New technologies and the growth of information: Alternative paths to education in developing countries - Ana Sekulovska-Jovkovska; Elizabeta Tosheva (UTMS Journal of Economics, 2021)
During the COVID-19 outbreak, when all human activities have moved from physical to virtual society, Western Balkan countries (WB6) had seen tremendous success with online learning platforms. The way forward was to promote remote learning and the use of online learning platforms, to continue supporting students to gain access to the necessary equipment for remote learning, and to provide teachers with digital learning opportunities on how to teach online, to share their resources and to give and receive feedback. The objective of this paper is to analyze alternative paths to education through the prism of online learning readiness. Student attributes required to engage in distance learning (e.g. knowledge of technology in use, time management, organization, selfmotivation, online technology interactions, etc.) vary greatly from student to student, so that large institutions are implementing efforts to address varying levels of readiness and preparedness that may influence student success. As central and local governments in developing countries continue to work on the implementation of educational policies and programs for the integration of information and communication technologies (ICT) in education, the need to assess and evaluate the extent to which such technologies are effective is increasing.
Keywords: I21; I28; O32; 330; online education; education; educational technology; universities; online learning readiness